Strategies of cell and cell-free therapies for periodontal regeneration: the state of the art - Xiuting Wang; Jinlong Chen; Weidong Tian (Stem Cell Research & Therapy, 2022)
Abstract Background Periodontitis often causes irrevocable destruction of tooth-supporting tissues and eventually leads to tooth loss. Currently, stem cell-based tissue engineering has achieved a favorable result in regenerating periodontal tissues. Moreover, cell-free therapies that aim to facilitate the recruitment of resident repair cell populations to injured sites by promoting cell mobilization and homing have become alternative options to cell therapy. Main text Cell aggregates (e.g., cell sheets) retain a large amount of extracellular matrix which can improve cell viability and survival rates after implantation in vivo. Electrostatic spinning and 3D bioprinting through fabricating specific alignments and interactions scaffold structures have made promising outcomes in the construction of a microenvironment conducive to periodontal regeneration. Cell-free therapies with adding biological agents (growth factors, exosomes and conditioned media) to promote endogenous regeneration have somewhat addressed the limitations of cell therapy. Conclusion Hence, this article reviews the progress of stem cell-based tissue engineering and advanced strategies for endogenous regeneration based on stem cell derivatives in periodontal regeneration.